Produção de carne de cabritos e digestibilidade utilizando levedura seca (Saccharomyces cerevisiae) - Freitas, Hanna Sakamoto (2009)
The objective of this work was to evaluate the quantitative characteristics of carcass, and qualitative of the loin and shoulder of kids ¾ Boer + ¼ Saanen and Saanen and to evaluate the feed intake, dry matter nutrients digestibility, nitrogen balance and to estimate nutrients total digestible of diets with inclusion of dry yeast replacing the soybean meal. Twenty-seven carcasses of 18 ¾ Boer + ¼ Saanen and nine Saanen noncastrated male goats were used with a slaughter weight of 30.1 ± 0.27 kg, to evaluate the carcass characteristics and qualitative characteristics of the loin and shoulder. The animals were distributed in a completely randomized design in factorial arrangement 2x3 (racial group x diet). The diets were made by adding dry yeast: soybean meal, soybean meal + dry yeast or dry yeast. The common ingredients were: oat hay (30% of DM), corn and mineral mix. The hot carcass weight, cold carcass weight, loss of cooling, true carcass yield and carcass compacity index were not affected (P>0.05) by treatments. otherwise, the group Saanen had higher value of carcass commercial yield, however, they had 15 days longer for reach the slaughter weight. The yield of commercial cuts were not affected (P>0.05) by treatments, but, significant interaction for shoulder yield was observed. The treatments did not influence the measures of loin, muscle:bone rate, cooking loss, slice shear force and centesimal composition. For proportion of muscle in the loin, the treatments showed interaction, verifying that the inclusion of yeast in the ration for group ¾ Boer + ¼ Saanen was higher. In shoulder the treatments did not influence the ratio of muscle, bone, humidity and ash content. However, for the group Saanen the ratio of bone and humidity content were higher and total lipids content was lower. For the digestibility were used five non-castrated male goats (31.8 ± 1.44 kg) housed in digestibility cages, in 5x5 latin square design. The rations were formulated with inclusion of dry yeast (0; 25; 50; 75; 100% of DM) replacing the soybean meal in diets for kid goats, the rations being composed of oat hay (30% of DM), ground corn, soybean meal and/or dry yeast and mineral supplement. The total feces (with canvas bags) and urine were collected for each experimental period, which constituted of 10 days of adaptation to the rations and five for collections. The dry matter intake and total carbohydrates were unchanged by the inclusion of dry yeast in rations. However, for: organic matter, crude protein, ether extract and neutral detergent fiber intake there were a quadratic effect. For the digestibility of ether extract there was negative linear effect with the inclusion of dry yeast in rations. The dry matter, organic matter, crude protein, total carbohydrates, neutral detergent fiber and total digestible nutrients digestibility showed quadratic effects. The nitrogen balance did not have any change with the inclusion of dry yeast in rations. The group ¾ Boer + ¼ Saanen had a higher precocity with the reduction of slaughter age resulting from the heterosis obtained from the crossing. Dry yeast can be included in rations for kid goats as protein source without change the feed intake of the dry matter and nitrogen balance, however, attention for maximum limits of its inclusion must be hard for not reduce the digestibility of dry matter and nutrients.